ANALISIS KECELAKAAN PENERBANGAN DI INDONESIA UNTUK PENINGKATAN KESELAMATAN PENERBANGAN - Eko Poerwanto; Uyuunul Mauidzoh (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2017)
Achievement level of aviation safety can be achieved with the proper function of all components of the system in the aviation industry which consists of airport operators, airline operators, air traffic operators and aircraft maintenance operator, as well as the regulations set by the regulator. Every incident should be investigated aviation accidents to fin d the cause. This is to provide appropriate recommendations so that the same airline accident does not happen again. The increasing number of flights that are needed with safety guarantees. So it is importance to analyzed routine flight accident to improve the safety performance of airlines. This research is descriptive analysis with qualitative methods. Flight accidents data that have investigated from NTSC and DGCA grouped causes are then recommendations have been made by the NTSC also grouped for each operator stakeholders. Improved system of aviation safety in Indonesia can be done with a thorough analysis based on the results of investigation of NTSC whose recommendations have been given to all stakeholders in the aviation industry. The results showed that the causes of flight accidents in Indonesia is dominated by the human factor the percentage reached 60%. The highest number of the recommendations given by the NTSC to DGCA as many as 208 recommendations during the period 2007-2014 but the trend o f declining. On other side of the trend of the recommendations given to aviation operators showed an increase. This shows an increase in the duty on DGCA to always supervise, and set the standard flight operations carried out by several airline operators in Indonesia.